Pediatric intensivists' perspective on managing adult critically ill patients during coronavirus disease-19 pandemic - H Michael Ushay; Shivanand S Medar; Pooja Nawathe; Pavanasam Ramesh; Giovanna Chidini; Manu Sundaram; Utpal S Bhalala (Wolters Kluwer Medknow Publications, 2021)
The novel corona virus pandemic has stretched health-care systems globally. In parts of countries such as USA, Italy, UK, and Spain, the adult health-care system has been overwhelmed by the sheer volume of patients requiring hospital admissions. Learning from other countries that have earlier peaks, various health-care organizations came up with plans providing guidance on preserving the functioning of health-care system in anticipation of a public health crisis. Coronavirus disease (COVID-19) has been less severe in children, and fewer children have required pediatric intensive care unit (PICU). For this reason, the surge plan to care for high number of critically ill adult patients with COVID-19 was to use PICU. There are various models on how to care for these patients in the surge capacities in the PICUs. We, hereby, reflect on our experience of managing the critically ill adult patients in PICUs in USA, UK, and Spain.